From Oranje Nassau to Pulau Laut : The Invest of Coal Mining In Southeast Kalimantan From 1845 to 1931 - Mansyur, Mansyur (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
European Industrial Revolution in the eighteenth century brought significant changes not only in Europe itself but also in other parts of the world, including Indonesia, which was used to be a country of the Dutch colony. The invention of steam-powered ships triggered the Dutch to use steam-powered vessels as the alteration of yachts, wind-powered ships, in the 19th century. In the beginning, the steam-powered ships used rotating wheels on the left and right sides; however, the ships finally used ordinary windmills or propellers. In the crisis year in 1930, Pulau Laut Mining Company production dropped so that it was closed down in the same year. The decrease and the lack of this production worsened the competition of other producer countries in the world market and the unstable coal market.